Beyond the COVID-19 Crisis : A Framework for Sustainable Government-To-Person Mobile Money Transfers - Prady, Delphine (IMF Working Papers; Working Paper ;, 2020)
During the 2020 pandemic, the majority of countries have provided income support to households at an unprecedented speed and scale. Social distancing measures and the large penetration of mobile phones in emerging markets and developing economies (EMDEs) have encouraged government-to-person (G2P) transfers through mobile platforms. This paper presents a comprehensive framework for sustainable money solutions in support of social assistance. The framework consists of eight building blocks that may help policymakers i) take stock and assess emergency fixes taken to scale up mobile money in a crisis context and ii) develop sustainable long-term solutions for mobile G2P transfers.